2016
DOI: 10.1007/s10443-016-9529-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential of Using Off-Axis 3D Woven Composites in Composite Joints’ Applications

Abstract: The effect of circular notch has been evaluated for three different architectures of three-dimensional (3D) carbon fibre woven composites (orthogonal, ORT; layer-to-layer, LTL; angle interlock, AI) through open-hole quasi-static tension and double-lap bearing strength tests in the off-axis (45°) direction. Damage characterisation is monitored using Digital Image correlation (DIC) for open-hole testing and X-ray Computed Tomography (CT) for double-lap bearing strength test. The off-axis notched 3D woven composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
(31 reference statements)
3
15
0
Order By: Relevance
“…This was attributed to the fact that in the half-hole test the load carrying yarns were cut along the cross section for testing. In the case of the double-lap test, the warp-loaded specimens demonstrated the highest stiffness but the off-axis loaded specimens had the highest bearing strength, which supports the argument proposed earlier by (Saleh et al 2016a) that although off-axis 3D woven composites demonstrate less stiffness, they possess significantly better damage resistance/tolerance capabilities up to failure.…”
Section: Bearing Strengthsupporting
confidence: 84%
See 3 more Smart Citations
“…This was attributed to the fact that in the half-hole test the load carrying yarns were cut along the cross section for testing. In the case of the double-lap test, the warp-loaded specimens demonstrated the highest stiffness but the off-axis loaded specimens had the highest bearing strength, which supports the argument proposed earlier by (Saleh et al 2016a) that although off-axis 3D woven composites demonstrate less stiffness, they possess significantly better damage resistance/tolerance capabilities up to failure.…”
Section: Bearing Strengthsupporting
confidence: 84%
“…Only one recent study by Saleh et al (Saleh et al 2016a) reported the notched response of 3D woven composites, in off-axis orientation, by an open hole tension test. The study considered three different architectures namely ORT, AI and LTL and focused only on the off-axis direction.…”
Section: Off-axismentioning
confidence: 99%
See 2 more Smart Citations
“…For aerospace applications, as reported by NASA, the X-37B and X-38 aircrafts employed a large number of C f /SiC composites in their nose cone [25], leading edge wing and engine components [11,26,27,29]. For nuclear applications, C f /SiC composites are used as the cladding materials in pressurized water reactors and flow channel insert materials in thermonuclear fusion reactors [29,30,32]. In most cases, typically, C f /SiC composite components are usually geometrically complex in shape and always need to join with other materials to form a certain engineering part.…”
Section: Introductionmentioning
confidence: 99%